Developing BIM-FM innovation technology acceptance framework - Sheikh Ali Azzran,; Tah, Joseph H.M.; Abanda, Henry (Penerbit Universiti Kebangsaan Malaysia, 2018)
The adoption of emerging technologies involving open Building Information Modeling (BIM) standards such as Construction Operation Building information exchange (COBie) and Industry Foundation Class (IFC) has been a challenge, especially in the facilities management (FM) domain. The objective of this study is to identify the key factors that influence the adoption of open BIM by investigating the reasons behind its low adoption in facilities management using an integrated framework adapted from the Technology Acceptance Model (TAM) and Innovation Diffusion Theory (IDT). The BIM-FM Innovation Technology Acceptance Model concentrates on six main constructs; Awareness of BIM, Compatibility of Computer Aided Facilities Management (CAFM) system, Observability, Trialability, Perceived usefulness, and Perceived ease of use. The framework was developed based on extensive literature review of BIM and FM, and informal discussions with industrial experts. This paper discusses these constructs. The major contribution to theory is the conceptualization of key factors that influence the adoption of open BIM standards. Results of this research may better facilitate the adoption of open BIM standards in facilities management. Findings may provide guidance for facilities managers to support the implementation and wider adoption of open BIM standards in the future.